Flume experiments for investigation of rainfall-induced slope failure - Hakro, M.R. (Trans Tech Publications Ltd, 2015)
The rainfall-induced slope failure is the major geo-hazard all over the world including Malaysia. Number of studies done already to investigate the process of slope failure, however the parameters that control the initiation of flowslide type of failure is still lacking. In tropical areas different mass movements occur from erosion to flow type of failure, in order to understand the mechanism will help to mitigate the posed risk. The flowslide is also type of slope failure that mostly occur in granular type soils, when initiated attain the higher velocity and fluid like motion, and it is dangerous than other types of landslides. The flowslide type of slope failure mainly due to rainfall. Field studies are timing consuming and expensive, while numerical studies requires lot of characteristics related to geology of the materials. Therefore laboratory flume experiments used in order to understand the mechanism and behavior of slope failure by changing different parameters such as density, rainfall intensity, thickness and initial moisture condition. The model slope prepared by sandy type of the soil and failure induced by artificial rainfall by installing the sprinklers above the model flume. During the experiments the pore pressure and moisture content were measured. From the detailed experimental study it was observed density of soil slope controls the initiation of the flowslide type failure. Small density of the soil slope suffers from flowslide type of the failure at smaller rainfall intensity. However in case of higher density even higher rainfall intensity accompanied with significant initial moisture conditions did not trigger the flowslide. The erosion gullies formed from toe to crest of the slope in the case of dense slope. The measurements of moisture content at the lower parts of the slope can be used as early warning of slope failure, however piezometers less reliable for prediction of slope failure in advance. Before large failure the settlement occur at the crest of the slope. Â© (2015) Trans Tech Publications.